PL04: Comparison of the cost and the quality of the care provided to low acuity patients in an emergency department and a walk-in clinic. (May 2019) - Berthelot, S.; Mallet, M.; Simonyan, D.; Guertin, J.; Moore, L.; Boilard, C.; Boulet, J.; Fortier, C.; Olivier, P.; Huard, B.; Vachon, K.; Lesage, A.; et al.
Abstract : Introduction : Low acuity patients have been controversially tagged as a source of emergency department (ED) misuse. Authorities for many Canadian health regions have set up policies so these patients preferably present to walk-in clinics (WIC). We compared the cost and quality of the care given to low acuity patients in an academic ED and a WIC of Québec City during fiscal year 2015-16.Methods : We conducted an ambidirectional (prospective and retrospective) cohort study using a time-driven activity-based costing method. This method uses duration of care processes (e.g., triage) to allocate to patient care all direct costs (e.g., personnel, consumables), overheads (e.g., building maintenance) and physician charges. We included consecutive adult patients, ambulatory at all time and discharged from the ED or WIC with a diagnosis of upper respiratory tract infection (URTI), urinary tract infection (UTI) or low back pain. Mean cost [95%CI] per patient per condition was compared between settings after risk-adjustment for age, sex, vital signs, number of regular medications and co-morbidities using generalized log-gamma regression models. Proportions [95%CI] of antibiotic prescription and chest X-Ray use in URTI, compliance with provincial guidelines on use of antibiotics in UTI, and column X-Ray use in low back pain were compared between settings using a Pearson Chi-Square test.Results : A total of 409 patients were included. ED and WIC groups were similar in terms of age, sex and vital signs on presentation, but ED patients had a greater burden of comorbidities. Adjusted mean cost (2016 CAN) of care was significantly higher in the ED than in the WIC (p < 0.0001) for URTI (78.42[64.85-94.82] vs. 59.43[50.43-70.06]), UTI (78.88[69.53-89.48] vs. 53.29[43.68-65.03]), and low back pain (87.97[68.30-113.32] vs. 61.71[47.90-79.51]). For URTI, antibiotics were more frequently prescribed in the WIC (44.1%[34.3-54.3] vs. 5.8%[1.2-16.0]; p < 0.0001) and chest X-Rays, more frequently used in the ED (26.9%[15.6-41.0] vs. 13.7%[7.7-22.0]; p = 0.05). No significant differences were observed in the compliance with guidelines on use of antibiotics in UTI and in the use of column X-Ray in low back pain.Conclusion : Total cost of care for low acuity patients is lower in walk-in clinics than in EDs. However, our results suggest that quality-of-care issues should be considered in determining the best alternate setting for treating ambulatory emergency patients.